The Application Of Legal Sanctions Against Content Creators Using Song Works Without Permission On Social Media Based On Law No. 28 Of 2014 On Copyright - Mardiana, Eka; Erniwati, Erniwati; Fitri, Aidil (Fakultas Hukum Dehasen, 2025)
Technological advances and the widespread use of social media have led to increased activity among content creators in creating and disseminating works, including the use of songs as elements in digital content. However, the use of copyrighted songs without permission raises legal issues related to copyright infringement. The issues raised in this study include: What is the form of application of legal sanctions against users of content creators without permission from song copyright owners on social media based on Law Number 28 of 2014 concerning Copyright, and what is the legal protection for users of content creators without permission from song copyright owners on social media according to statutory regulations. The method used is normative juridical with a statutory regulatory approach and literature study. Legal protection in this case is divided into two forms, namely preventive protection and repressive protection. Based on the results of the study, Article 9 paragraph (3) of the Law states that everyone is prohibited from reproducing or utilizing copyrighted works for commercial purposes without permission from the creator or copyright holder. Furthermore, Article 113 paragraph (1) stipulates that copyright infringement can be subject to criminal sanctions or fines. This law also provides a mechanism for resolving disputes through legal channels, both litigation and non-litigation. Therefore, it is crucial for content creators to understand and respect copyright by obtaining official permission or a license before using music or songs in their work.